2017
DOI: 10.1088/1751-8121/aa86c7
|View full text |Cite
|
Sign up to set email alerts
|

Dimension reduction for stochastic dynamical systems forced onto a manifold by large drift: a constructive approach with examples from theoretical biology

Abstract: Systems composed of large numbers of interacting agents often admit an effective coarsegrained description in terms of a multidimensional stochastic dynamical system, driven by small-amplitude intrinsic noise. In applications to biological, ecological, chemical and social dynamics it is common for these models to posses quantities that are approximately conserved on short timescales, in which case system trajectories are observed to remain close to some lower-dimensional subspace. Here, we derive explicit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 68 publications
0
41
0
Order By: Relevance
“…The full calculation is too long to reproduce here, however a clear and coherent explanation is given in Ref. [51]. There it is shown that if a system has M variables and a one-dimensional slow-subspace, then the equation for the reduced/effective dynamics can be expressed by…”
Section: Revealing Noise-induced Selection Via Fast Variable Eliminationmentioning
confidence: 91%
“…The full calculation is too long to reproduce here, however a clear and coherent explanation is given in Ref. [51]. There it is shown that if a system has M variables and a one-dimensional slow-subspace, then the equation for the reduced/effective dynamics can be expressed by…”
Section: Revealing Noise-induced Selection Via Fast Variable Eliminationmentioning
confidence: 91%
“…Then using methods outlined in recent work (Constable et al. ; Parsons and Rogers ), which built off of standard techniques (Katzenberg ; Berglund and Gentz ), the slow timescale dynamics of p are governed by the stochastic differential equation (SDE) truerightdp=left(νfalse(12pfalse)εβfalse(xpfalse)pfalse(1pfalse))afalse(pfalse)dtleft+0.28emp(1p)normalΩRfalse(xpfalse)σ2(p)1/2dWt,0.33em…”
Section: Modelmentioning
confidence: 99%
“…Therefore, we wish to reduce it to a more tractable form. To do so, we observe that since selection is weak and mutations are rare, system (1) admits what is commonly referred to as a "slow manifold" (Berglund and Gentz 2006;Parsons and Rogers 2017), which in this case is a curve in (x, y 1 , y 2 )-space satisfying β(x) = μ(x). The reason that this curve is referred to as a slow manifold is that in the vicinity of this curve, the per capita growth rate of the different pathogen strains is very small (since mutations are rare and selection is weak), and so changes in the composition of the pathogen population occur slowly.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…An SDE for heteroplasmy forced onto the steady state line in the high-churn limit It has been demonstrated that SDE descriptions of stochastic systems which possess a globally-attracting line of steady states may be formed in the long-time limit by forcing the state variables onto the steady state line (Constable et al, 2016;Parsons and Rogers, 2017). Such descriptions may be formed in terms of a parameter which traces out the position on the steady state line, hence reducing a high-dimensional problem into a single dimension (Constable et al, 2016;Parsons and Rogers, 2017). In our case, heteroplasmy is a suitable parameter to trace out the position on the steady state line.…”
Section: Fokker-planck Equation For Chemical Reaction Networkmentioning
confidence: 99%